The new way of Dabigatran reversal – Idarucizumab - Ciechański, Erwin; Ciechański, Krystian; Ciechańska, Magda; Szponar, Jarosław (Journal of Education, Health and Sport, 2019)
Since last few years a popularity of new oral anticoagulants significantly raised. There are following main direct oral anticoagulants (DOAC) used in therapy: Dabigatran, Rywaroxaban, Apixaban, Endoxaban. Dabigatran (Pradaxa) is the first oral direct thrombin inhibitor approved by FDA in stroke prevention in atrial fibrillation (AF). Anticoagulant effect occurs through direct thrombin binding. Unlike the vitamin K antagonists such as warfarin or acenokumarol, therapy with dabigatran has faster onset and offset action, doesn’t require routine monitoring has much less interactions. The main problem of treatment with dabigatran was difficulty in reversal of anticoagulant effect and overdose. Since three years the new antidote for dabigatran is available – Idarucizumab (Praxbind). Main indications for such use are dabigatran overdose, need of fast effect reversal before any interventions and life threatening bleeding. Despite other ways of anticoagulant effect reversal such as transfusion of plasma coagulation factors Idarucizumab is still highly recommended for direct use. Aim of this study is to review the new way of dabigatran reversal - Idarucizumab .